A Long Way to Complexity: Nonlinear "Growth Stages" and Spatially Uncoordinated Settlement Expansion in a Compact City (Athens, Greece). Issue 2 (15th May 2022) - Salvati, Luca
Abstract: Recent urbanization trends reflect an increasing dependence on regional economic transformations, local population dynamics, and planning constraints, becoming intrinsically complex and nonlinear. Following this assumption, the present study proposes a new approach for the analysis of long‐term urban expansion in a compact metropolitan region (Athens, Greece), clarifying the importance of spatial heterogeneity and volatility in building activity over more than one century. A spatially explicit statistical approach was used to define a development cycle reflecting the stratification of heterogeneous waves of compact and dispersed urbanization at municipal scale. While resulting in distinctive spatial patterns of building activity, long‐term urban growth emerged as a multifaceted response to market stimuli, social change, and diversified territorial contexts. Results of a spatially explicit analysis of long‐term urban expansion based on official statistics shed further light on processes of metropolitan growth and change, and contribute to design integrated strategies enhancing spatial coordination and a more balanced socioeconomic development of contemporary cities.